2007
DOI: 10.1039/b616100f
|View full text |Cite
|
Sign up to set email alerts
|

Chemoenzymatic synthesis of trans-dihydrodiol derivatives of monosubstituted benzenes from the corresponding cis-dihydrodiol isomers

Abstract: Enantiopure trans-dihydrodiols have been obtained by a chemoenzymatic synthesis from the corresponding cis-dihydrodiol metabolites, obtained by dioxygenase-catalysed arene cis-dihydroxylation at the 2,3-bond of monosubstituted benzene substrates. This generally applicable, seven-step synthetic route to trans-dihydrodiols involves a regioselective hydrogenation and a Mitsunobu inversion of configuration at C-2, followed by benzylic bromination and dehydrobromination steps. The method has also been extended to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…This instability presents problems for storage and safe transportation. Regioselective hydrogenation of the unsubstituted alkene bond of cis ‐dihydrodiol metabolites of mono‐substituted benzenes, e.g., 1b–e , can, in principle, give very stable cis ‐tetrahydrodiol adducts 2b–e 59. The adducts still contain the original two chiral centres and much of the original functionality and have the advantage of being stable at room temperature.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This instability presents problems for storage and safe transportation. Regioselective hydrogenation of the unsubstituted alkene bond of cis ‐dihydrodiol metabolites of mono‐substituted benzenes, e.g., 1b–e , can, in principle, give very stable cis ‐tetrahydrodiol adducts 2b–e 59. The adducts still contain the original two chiral centres and much of the original functionality and have the advantage of being stable at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Halogenated cis ‐dihydrodiols 1b–e , (Scheme ), were found to be more challenging substrates for selective alkene reduction, as in addition to the usual aromatisation side reaction, hydrogenolysis of the carbon‐halogen bond was also observed. Thus, the reduced yield of cis ‐tetrahydrodiols 2d and 2e made the otherwise synthetically versatile bromo‐ and iodo‐ cis ‐dihydrodiol derivatives, 1d and 1e , less attractive chiral precursors 6–9. In this context, earlier studies6,9 showed that partial catalytic hydrogenation of cis ‐dihydrodiols 1c and 1d using Rh/Al 2 O 3 catalyst in THF or EtOH solvent resulted in good yields (85%) of adducts 2c , 2d with minimal evidence of hydrogenolysis of the carbon‐halogen bond or aromatisation occurring.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Merck Kieselgel type 60F 254 analytical plates were used for TLC. Samples of cis ‐dihydrodiols 2a–2h ,26 cis ‐tetrahydrodiols 5c and 5h ,19,20 and the phosphines 22 and 23 46 were available from earlier studies. The cis‐ dihydrodiols 2a–2h had earlier been established as single enantiomers, i.e., enantiopure, (>98% ee ) by CSPHPLC and NMR analysis methods 26.…”
Section: Methodsmentioning
confidence: 99%
“…Two different heterogeneous catalysts have been used in the disproportionation of benzene cis ‐dihydrodiols 2 [R=H, F, Cl, Br, CN, Me, t ‐Bu, CF 3 , CH(OH)CF 3 ] to yield both the corresponding cis ‐tetrahydrodiols 5 and catechols 4 (Pd‐C),19 and in the partial hydrogenation of halogenated benzene cis ‐dihydrodiols 2 (R=F, Cl, Br, I, CF 3 ) to give the cis ‐tetrahydrodiol derivatives 5 (Rh‐Al 2 O 3 ) 20. However, problems were encountered due to the instability of some cis ‐dihydrodiols, e.g., 2 (R=I),20 resulting in the formation of the corresponding o ‐ or m ‐phenols 3 . Improved methods have recently been developed to minimise phenol formation and to optimise the yields of cis ‐tetrahydrodiols 5 from the regioselective catalytic hydrogenation of the corresponding cis ‐dihydrodiols 2 (R=Br, I, unpublished data).…”
Section: Introductionmentioning
confidence: 99%